The Plant Nuclear Envelope and Its Role in Gene Transcription - Bishop, Jade; Swan, Hetty; Valente, Francesco; Nützmann, Hans-Wilhelm (Frontiers in Plant Science, 2021)
Chromosomes are dynamic entities in the eukaryotic nucleus. During cell development and in response to biotic and abiotic change, individual sections as well as entire chromosomes re-organise and reposition within the nuclear space. A focal point for these processes is the nuclear envelope providing both barrier and anchor for chromosomal movement. In plants, positioning of chromosome regions and individual genes at the nuclear envelope has been shown to be associated with distinct transcriptional patterns. Here, we will review recent findings on the interplay between transcriptional activity and gene positioning at the nuclear periphery. We will discuss potential mechanisms of transcriptional regulation at the nuclear envelope and outline future perspectives in this research area.